Asymmetry and integration of cellular morphology in Micrasterias compereana - Neustupa, Jiří (BMC evolutionary biology, 2017)
BACKGROUND: Unicellular green algae of the genus Micrasterias (Desmidiales) have complex cells with multiple lobes and indentations, and therefore, they are considered model organisms for research on plant cell morphogenesis and variation. Micrasterias cells have a typical biradial symmetric arrangement and multiple terminal lobules. They are composed of two semicells that can be further differentiated into three structural components: the polar lobe and two lateral lobes. Experimental studies suggested that these cellular parts have specific evolutionary patterns and develop independently. In this study, different geometric morphometric methods were used to address whether the semicells of Micrasterias compereana are truly not integrated with regard to the covariation of their shape data. In addition, morphological integration within the semicells was studied to ascertain whether individual lobes constitute distinct units that may be considered as separate modules. In parallel, I sought to determine whether the main components of morphological asymmetry could highlight underlying cytomorphogenetic processes that could indicate preferred directions of variation, canalizing evolutionary changes in cellular morphology. RESULTS: Differentiation between opposite semicells constituted the most prominent subset of cellular asymmetry. The second important asymmetric pattern, recovered by the Procrustes ANOVA models, described differentiation between the adjacent lobules within the quadrants. Other asymmetric components proved to be relatively unimportant. Opposite semicells were shown to be completely independent of each other on the basis of the partial least squares analysis analyses. In addition, polar lobes were weakly integrated with adjacent lateral lobes. Conversely, higher covariance levels between the two lateral lobes of the same semicell indicated mutual interconnection and significant integration between these parts. CONCLUSIONS: Micrasterias cells are composed of several successively disintegrated parts. These integration patterns concurred with presumed scenarios of morphological evolution within the lineage. In addition, asymmetric differentiation in the shape of the lobules involves two major patterns: asymmetry across the isthmus axis and among the adjacent lobules. Notably, asymmetry among the adjacent lobules may be related to evolutionary differentiation among species, but it may also point out developmental instability related to environmental factors.
Keywords: Desmidiales; biologická evoluce; Morphological asymmetry; morfogeneze; Geometric morphometrics; Micrasterias; Morphological integration; Morphogenesis; Green algae; Biological Evolution